Making Sense Of Mindfulness In Indonesian Elementary Schools: A Phenomenological Exploration Of Pupils’ Lived Experiences Of Concentration And Memory Within The “Merdeka Belajar” Context - Lauw Acep; Dewi Oktaviany (Jurnal Ilmu Pendidikan Nasional (JIPNAS), 2025)
This study aims to elucidate the essence of Indonesian elementary school students' lived experiences of mindfulness meditation and how it shapes their perceptions of concentration and memory in the context of "Freedom to Learn." A hermeneutic-phenomenological study was conducted with five students in grades 4-5. Data were generated through in-depth conversations and participant observations during a four-week classroom mindfulness program and analyzed through phenomenological reduction and thematic synthesis. The research findings indicate that the unchanging essence, namely "a shift from an anxious mind to a calm mind that opens up space for learning," is expressed through four interrelated themes: perceived emotional calm, sustained attention, easier recall, and positive appreciation of quiet moments. The study concludes that mindfulness is not simply a technique, but a pedagogical way of life that begins with learning; integrating brief, mindful pauses can foster reflective, calm, and independent learners aligned with the Pancasila Student Profile.